ANALISIS KETELITIAN PENGUKURAN BASELINE PANJANG GNSS DENGAN MENGGUNAKAN PERANGKAT LUNAK GAMIT 10.4 DAN TOPCON TOOLS V.7 - Maulana Eras Rahadi; Moehammad Awaluddin; L. M. Sabri (Jurnal Geodesi UNDIP, 2013)
GPS data processing with long baseline (over 100km) require special handling, is caused by determining the value of ambiguity. Distance and number of reference stations have a significant factor on the quality of the network configuration, if both factors have been determined with good accuracy the value it will provide accurate positioning and precision.This study uses observation data with a baseline length of more than 20 km it will tied to the base station GNSS CORS Undip. Another the measurement will be tied to the GNSS CORS BIG (Badan Informasi Geospasial) which has a 0-orde accuracy. By using these two reference stations will be able to know, how much the accuracy each reference station to the accuracy of the coordinates of each observation point. Seeing the factor of long baseline observations in this study, in the processing of the observation data will be processed with scientific software GAMIT 10.4 and commercial software Topcon Tools V.7The research in this paper shows the average standard deviation value of the processing results using GAMIT 10.4 is 0,020 m while the standard deviation value of the processing results using Topcon Tools V.7 is 0,028 m. Keywords: GNSS CORS, Long Baseline, GAMIT, Topcon